2009
DOI: 10.1037/a0017198
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of familial acceptance–rejection among transwomen of color.

Abstract: Because of the stigma associated with transgenderism, many transwomen (biological males who identify as female or transgender) experience rejection or abuse at the hands of their parents and primary caregivers as children and adolescents. The Parental Acceptance-Rejection (PAR) theory indicates that a child's experience of rejection may have a significant impact on their adult lives. The purpose of this study was to conduct a qualitative analysis of adult transwomen of color's experiences with caregivers, guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
141
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(144 citation statements)
references
References 34 publications
3
141
0
Order By: Relevance
“…For example, findings suggest that transgender women who have access to transition-related medical care, such as cross-sex gender affirmative surgeries, experience improved mental health and better quality of life compared to their non-medically-transitioning counterparts (Bauer et al, 2015;de Vries et al, 2014;Gómez-Gil et al, 2012;Rotondi et al, 2011;Wilson, Chen, Arayasirikul, Wenzel, & Raymond, 2015). Further, familial support represents another important aspect of social affirmation, as findings suggest that lower rates of family rejection and greater support are significantly associated with better health outcomes, greater perceived safety in public settings, higher self-esteem, less depressive symptoms, lower suicidal ideation, and better quality of life among transgender women (Bauer et al, 2015;Factor & Rothblum, 2008;Koken et al, 2009;Ryan, Russell, Huebner, Diaz, & Sanchez, 2010).In accordance with Kozee and colleagues (2012), we propose psychological gender affirmation is also critical to the well-being of transgender populations. Kozee and colleagues (2012) posit that feeling comfortable with one's own gender identity is a facet of gender congruency, which they define as the degree to which individuals "feel genuine, authentic, and comfortable within their external appearance/presence and accept their genuine identity rather than the socially prescribed identity".…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…For example, findings suggest that transgender women who have access to transition-related medical care, such as cross-sex gender affirmative surgeries, experience improved mental health and better quality of life compared to their non-medically-transitioning counterparts (Bauer et al, 2015;de Vries et al, 2014;Gómez-Gil et al, 2012;Rotondi et al, 2011;Wilson, Chen, Arayasirikul, Wenzel, & Raymond, 2015). Further, familial support represents another important aspect of social affirmation, as findings suggest that lower rates of family rejection and greater support are significantly associated with better health outcomes, greater perceived safety in public settings, higher self-esteem, less depressive symptoms, lower suicidal ideation, and better quality of life among transgender women (Bauer et al, 2015;Factor & Rothblum, 2008;Koken et al, 2009;Ryan, Russell, Huebner, Diaz, & Sanchez, 2010).In accordance with Kozee and colleagues (2012), we propose psychological gender affirmation is also critical to the well-being of transgender populations. Kozee and colleagues (2012) posit that feeling comfortable with one's own gender identity is a facet of gender congruency, which they define as the degree to which individuals "feel genuine, authentic, and comfortable within their external appearance/presence and accept their genuine identity rather than the socially prescribed identity".…”
mentioning
confidence: 76%
“…Numerous studies have reported higher prevalence of psychological distress, including depressive symptoms, low self-esteem, and suicidal ideation in community samples of transgender women (MacCarthy, Reisner, Nunn, PerezBrumer, & Operario, 2015;Operario & Nemoto, 2010). Due to their gender identity or expression, transgender people experience high levels of gender-based social oppression, or transphobia, including everyday discrimination, family rejection, and hate crimes (Bazargan & Galvan, 2012;Bradford, Reisner, Honnold, & Xavier, 2012;Koken, Bimbi, & Parsons, 2009;Lombardi, Wilchins, Priesing, & Malouf, 2002;Nuttbrock et al, 2010). Scholars have proposed that adverse mental health outcomes in transgender populations are a result of this gender-specific social oppression (Bockting, Miner, Swinburne Romine, Hamilton, & Coleman, 2013;Goldblum et al, 2012;Haas et al, 2010;Nuttbrock et al, 2013;Reisner, Gamarel, Dunham, Hopwood, & Hwahng, 2013).…”
mentioning
confidence: 99%
“…In terms of rejection, Koken, Bimbi and Parsons (2009) found that, amongst their sample of 20 trans women of colour living in the United States, 40% experienced hostility and 40% experienced indifference from their families of origin (these categories were not mutually exclusive). Koken and colleagues suggest that rejection from families of origin can play a determining role in poor mental health outcomes for trans women of colour.…”
Section: Families Of Originmentioning
confidence: 99%
“…Pursuant to parental acceptance-rejection theory, children's experience of rejection has significant impacts on their adult lives, whereas positive relationships with family can provide strength and refuge from harsh social environments outside the family (Koken et al, 2009;Rohner, Khaleque, & Cournoyer, 2005). In a national study of predominately White transgender adults and their nontransgender siblings, transgender individuals perceived less social support from family compared to their nontransgender biological sisters (Factor & Rothblum, 2007).…”
Section: Social Support and Interpersonal Relationships With Family Amentioning
confidence: 99%